2022
DOI: 10.3390/jof8040330
|View full text |Cite
|
Sign up to set email alerts
|

DNA Metabarcoding and Isolation by Baiting Complement Each Other in Revealing Phytophthora Diversity in Anthropized and Natural Ecosystems

Abstract: Isolation techniques supplemented by sequencing of DNA from axenic cultures have provided a robust methodology for the study of Phytophthora communities in agricultural and natural ecosystems. Recently, metabarcoding approaches have emerged as new paradigms for the detection of Phytophthora species in environmental samples. In this study, Illumina DNA metabarcoding and a conventional leaf baiting isolation technique were compared to unravel the variability of Phytophthora communities in different environments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 91 publications
(169 reference statements)
3
8
0
Order By: Relevance
“…The major advantage of this combined approach is that baiting allows to obtain Phytophthora cultures useful for a better knowledge of isolates and Koch’s postulates validation. As expected, DNA metabarcoding revealed a higher number of Phytophthora taxa than baiting [ 85 , 88 ]. Sometimes, the identified taxa were not the same between the two methods [ 88 ], in other cases the two approaches revealed very similar Phytophthora communities [ 87 ].…”
Section: Metabarcodingsupporting
confidence: 67%
See 1 more Smart Citation
“…The major advantage of this combined approach is that baiting allows to obtain Phytophthora cultures useful for a better knowledge of isolates and Koch’s postulates validation. As expected, DNA metabarcoding revealed a higher number of Phytophthora taxa than baiting [ 85 , 88 ]. Sometimes, the identified taxa were not the same between the two methods [ 88 ], in other cases the two approaches revealed very similar Phytophthora communities [ 87 ].…”
Section: Metabarcodingsupporting
confidence: 67%
“…As expected, DNA metabarcoding revealed a higher number of Phytophthora taxa than baiting [ 85 , 88 ]. Sometimes, the identified taxa were not the same between the two methods [ 88 ], in other cases the two approaches revealed very similar Phytophthora communities [ 87 ].…”
Section: Metabarcodingsupporting
confidence: 67%
“…‘ kelmania ’), a riddle that cannot be solved without examination of pure cultures. Comparative studies on Phytophthora population compositions obtained by culture-dependent and metabarcoding methods showed that both techniques complemented each other [ 5 , 94 , 95 , 96 ]. Currently, several web-accessible databases have been developed to support accurate and rapid identification of Phytophthora species ( , and , accessed on 19 December 2022).…”
Section: Phytophthora Species Diversity In Plant Nurseriesmentioning
confidence: 99%
“…The Phyto-Threats project's metabarcoding protocol used nested PCR primers designed to target the Internal Transcribed Spacer 1 marker sequence (ITS1; a genomic region located between 18S and 5.8S rRNA genes in eukaryotes) of Phytophthora and related plant pathogenic oomycete (Scibetta et al, 2012). This approach is the current de facto standard within the oomycete community (Robideau et al, 2011), and these primers have been used in conjunction with THAPBI PICT in recent Phytophthora surveys (Vélez et al, 2020;La Spada et al, 2022). PICT was short for Phytophthora ITS1 Classification Tool.…”
Section: Introductionmentioning
confidence: 99%